Effect of impact loading on structural properties of multi-layered Ta/Cu, Nb/Cu and Fe/Cu plates fabricated by single-shot explosive welding. Issue 1 (1st December 2022) - Paul, H; Miszczyk, M M; Prażmowski, M; Chulist, R; Petrzak, P; Schell, N; Fatemi, M
Abstract : In this work, three eleven-layered composite plates based on Cu (six layers) and one of the reactive metals such as Ta, Nb or Fe (five layers) fabricated using a single-shot explosive welding process were studied. The morphology and phase composition of the interfacial layers were thoroughly investigated using scanning (SEM) and transmission (TEM) electron microscopy. The microstructural and chemical composition analyses were then correlated with micro-hardness measurements to evaluate the mechanical properties of the interfacial layers. It was found that layers near the interfaces exhibited a complex and hierarchical microstructure on various levels. Optical microscopy characterization confirmed the high quality of the composites, without voids or layers delamination. SEM analyses showed that the solidified melt regions unveiled different morphologies but always consisted of a mixture of pure Cu and Ta, Nb or Fe elements. Quantitative nano-scale analysis using TEM revealed that nanoparticles and small dendrites dominated the reaction regions. Although no brittle intermetallics were observed near all interfaces of all composites, the microhardness of the solidified melts was 2-3 times higher than those of the sheets in the annealed state.